2018
DOI: 10.1371/journal.pone.0197741
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Americanization of English in space and time

Abstract: As global political preeminence gradually shifted from the United Kingdom to the United States, so did the capacity to culturally influence the rest of the world. In this work, we analyze how the world-wide varieties of written English are evolving. We study both the spatial and temporal variations of vocabulary and spelling of English using a large corpus of geolocated tweets and the Google Books datasets corresponding to books published in the US and the UK. The advantage of our approach is that we can addre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(50 citation statements)
references
References 40 publications
4
45
0
1
Order By: Relevance
“…In this respect, it is worth mentioning that the role of a committed minority has been investigated in the context of various multi agent models where it has been shown to play an important role on the final consensus provided its size exceeds a certain threshold [6,[52][53][54], as observed also in recent laboratory experiments [55]. Third, we focused on the case where the competition takes place between two alternative norms, but more complex cases where more conventions concur to the process of norm change could exist [26]. Fourth, the model we introduced describes the process of norm change for an isolated linguistic group and does not address the important case of language change resulting from the contact between two linguistically independent populations or conflict between different languages [7].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this respect, it is worth mentioning that the role of a committed minority has been investigated in the context of various multi agent models where it has been shown to play an important role on the final consensus provided its size exceeds a certain threshold [6,[52][53][54], as observed also in recent laboratory experiments [55]. Third, we focused on the case where the competition takes place between two alternative norms, but more complex cases where more conventions concur to the process of norm change could exist [26]. Fourth, the model we introduced describes the process of norm change for an isolated linguistic group and does not address the important case of language change resulting from the contact between two linguistically independent populations or conflict between different languages [7].…”
Section: Resultsmentioning
confidence: 99%
“…The phenomenon of 'Americanization' of English [26] is not limited to spelling but includes also the introduction of different words or expression which over time replaced the British ones. Recent works [26,49]…”
Section: British English Vs American Englishmentioning
confidence: 99%
“…Human communication systems [linguistic vocalisations (e.g. British English, American English, Singapore English ‘Singlish’, Indian English ‘Hinglish’ and Kenyan English (Pederson, ; Mesthrie & Bhatt, ; Gonçalves et al ., ); gestures – e.g. British ‘Victory‐sign’ and ‘Thumbs‐up’, and American ‘OK‐circle‐sign’ (Morris, ); facial expressions – e.g.…”
Section: Theories Of the Origins Of Languagementioning
confidence: 99%
“…Then, it may be that British English authors and editors are being influenced by American publications and the language used therein. Indeed, some studies have found a general ‘Americanization’ of English across the globe [12, 13], meaning that the various varieties of English used across the world are becoming more aligned with American English. Finally, it may be that average British users of Twitter are more resistant to the change.…”
Section: Methods and Resultsmentioning
confidence: 99%